IMPROVEMENT OF THE LEGAL FRAMEWORK FOR REGULATING INTERNATIONAL AND NATIONAL RELATIONS ARISING IN THE PROCESS OF DEVELOPMENT OF BLOCKCHAIN TECHNOLOGIES (World Bulletin of Social Sciences, 2025)
This scientific article is devoted to a scientific analysis of the problems of regulating new legal relations arising at the international and national levels as a result of the rapid development of blockchain technologies (including crypto-assets, smart contracts, and DeFi). The main topic of the article is legal disputes arising from the decentralized and cross-border nature of the blockchain. Emphasis will also be placed on topics such as the jurisdiction of which state resolves disputes and how consumer rights are protected. The study examines the experience of Western Europe, the USA, and East Asian countries on this issue using various methods and compares it with the existing national legislative framework of the Republic of Uzbekistan.